Antimicrobial resistance modulation of MDR E. coli by antibiotic coated ZnO nanoparticles. (November 2020) - Anwar, Muhammad Ahsan; Aqib, Amjad Islam; Ashfaq, Khurram; Deeba, Farrah; Khan, Muhammad Kasib; Khan, Shanza Rauf; Muzammil, Iqra; Shoaib, Muhammad; Naseer, Muhammad Aamir; Riaz, Tanzeel; Tanveer, Qaisar; Sadiq, Masood; et al.
Abstract: We evaluated three types of total six preparations against multidrug resistant E. coli i) three antibiotic coated ZnO nanoparticles (gentamicin coated nanoparticle-GNp; chloramphenicol coated nanoparticles-CNp; and both gentamicin & chloramphenicol coated nanoparticle-GCNp), ii) ZnO nanoparticle alone-Np, and iii) two antibiotics used in single (Gentamicin-G; and Chloramphenicol-C). A total of n = 200 sub-clinically positive mastitic milk samples of bovine origin were processed for isolation of MDR E. coli using microbiological and clinical laboratory & standard institute's protocols. ZnO Nps were prepared from zinc acetate dihydrate (Zn (CH3 COO)2 . 2H2 O), polyethylene glycol (C2n H4n+2 On+1 ), and urea (CH₄N₂O) by standard chemical protocol. Nps were characterized by XRD and STEM analyses while coating of antibiotics on Nps was confirmed by UV–Visible spectrophotometric analysis. Analysis of variance and student t- test were applied at 5% probability using SPSS version 22 statistical software for inferences on obtained data. There was significantly ( p < 0.05) lowest minimum inhibitory concentrations (MICs) and highest zone of inhibitions (ZOIs) in case of GCNp (10.42 ± 4.51 μg/mL & 22.00 ± 1.00 mm) followed by GNp (20.79 ± 8.95 μg/mL & 20.00 ± 1.00 mm) and then CNp (25.96 ± 8.95 μg/mL & 12.33 ± 0.57 mm). Percentage increase in ZOI were expressed as 135.8, 78.43, and 312.76% by GCNp when compared with that of G, C, and Np, respectively. GNp and CNp coated preparations exhibited 114.36 and 275.73% increase in ZOI than to that of G and C, respectively. Similar trend was found in percentage reduction of MICs of preparations. Highest filamentation, indicator of bacterial damage, of E. coli was noted at MIC of GCNp followed by GNp and CNp. The study concluded antibiotic coated ZnO nanoparticles significant candidates modulating antibiotic resistance in MDR E. coli . Highlights: Multidrug resistant E. coli is becoming superbug Nanoparticles are alternative antibacterial candidates. Antibiotics coating on Zinc Oxide nanoparticle modulated resistance of MDR E. coli . Coated preparation were significant antibacterial candidates than to their single use. Filamentation was higher at lowest concentration of antibiotic coated nanoparticles.